Death of a child and parental wellbeing in old age: Evidence from Taiwan - Lee, Chioun (2013)
The death of a child is one of the most traumatic events that a parent can experience. The psychological and physical consequences of bereavement are well established, and the consequences are more severe for mothers than fathers. However, little is known about how the death of an adult child affects parental wellbeing in old age or how the deceased child’s sex may moderate the association. We use data from the Taiwanese Longitudinal Study of Aging (TLSA) to investigate how the death of a son or a daughter differentially affects the wellbeing of older parents, measured by depressive symptoms and self-rated health. We find that for mothers, a son’s death is associated with an increase in depressive symptoms and a decline in self-rated health, but fathers’ health is not adversely affected by a son’s death. There is little evidence that a daughter’s death has a negative effect on either maternal or paternal wellbeing. We situate these findings within their social and cultural contexts and discuss social policies that would reduce gender and health inequality.